2016
DOI: 10.1016/j.physletb.2016.07.064
|View full text |Cite
|
Sign up to set email alerts
|

Late time cosmic acceleration from natural infrared cutoff

Abstract: In this paper, inspired by the ultraviolet deformation of the Friedmann-Lemaître-Robertson-Walker geometry in loop quantum cosmology, we formulate an infrared-modified cosmological model. We obtain the associated deformed Friedmann and Raychaudhuri equations and we show that the late time cosmic acceleration can be addressed by the infrared corrections. As a particular example, we applied the setup to the case of matter dominated universe. This model has the same number of parameters as ΛCDM, but a dynamical d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Other than these two, recently, cosmologists and theoretical physicists have been successful in developing other interesting and convincing approaches. In [21], the phenomenon is explained by the infrared corrections. Narain [22] predicts that an Ultraviolet Complete Theory leads to the expansion.…”
Section: Introductionmentioning
confidence: 99%
“…Other than these two, recently, cosmologists and theoretical physicists have been successful in developing other interesting and convincing approaches. In [21], the phenomenon is explained by the infrared corrections. Narain [22] predicts that an Ultraviolet Complete Theory leads to the expansion.…”
Section: Introductionmentioning
confidence: 99%
“…Also in [21] it is shown that by taking GUP in the context of extra dimensions theories, there is a possibility to agree with the outcomes of LHC which claims no black holes are recognizable around 5 TeV [22]. Since a deformation of Heisenberg uncertainty principle affects various quantum phenomena, some efforts have been made to understand phenomenological aspects of GUP models in the context of astrophysics, cosmology and high energy physics in recent years, see for instance [23][24][25][26][27][28][29][30][31]. The consequence of GUP on the physics of white dwarf stars also studied in [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, studies carried out so far, confirm the point that the natural cutoff approaches make remarkable contributions in cosmological and astrophysical systems, for instance we can mention the Refs. [39][40][41][42]. In this paper, the QGP phase includes two massless quark flavors with zero chemical potential which at a HG-QGP phase thermodynamic equilibrium is affected by the underlying GUP modifications.…”
Section: Introductionmentioning
confidence: 99%